Narrative conceptions of knowledge towards understanding teacher attrition - Downey, C. Aiden; Clandinin, D. Jean; Schaefer, Lee (Advances in research on teaching ;, 2014)
The book volume shares six narrative accounts, which offer glimpses into the teachers' lives, which are composed with attention to place, temporality, and personal and social dimensions. By inquiring narratively into the experiences of these teachers, the book identifies the complex ways in which the teachers' personal practical knowledge is shaped by their personal knowledge landscapes as well as professional knowledge landscapes. Questions are raised about the implications of seeing teacher attrition as a process rather than singular event, that is, as a process of coming to tell a story to leave by, for our understandings of teacher knowledge and identity. As we shift from seeing "beginning teachers" to seeing "teachers as beginning", that is, as seeing teachers as people with experiences of personal and professional becoming, we shift from seeing them as more than content knowledge and pedagogic skills, but as people in the midst of living lives. This narrative and more holistic understanding of teacher knowledge and identity will help preservice teacher education programs, schools and school districts to better sustain people as they begin to teach and become teachers.